Evaluating the potential of ultraviolet irradiation for the disinfection of microbiologically polluted irrigation water - Olivier, Francois (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc Food Sc)--Stellenbosch University, 2015.